Gershwin country [compact disc] - Feinstein, Michael; Gershwin, George, 1898-1937 (Craft Recordings, 2022)
New duets collection from the GRAMMY® and Emmy-nominated entertainer Michael Feinstein, who reimagines the timeless Gershwin songbook through the contemporary lens of country music. The album pairs Feinstein with some of the biggest names in country, including Dolly Parton, Alison Krauss, Brad Paisley, Rosanne Cash and many more.